CHANGES IN PLATELET INDICES IN PATIENTS WITH RHEUMATOID ARTHRITIS –A CROSS SECTIONAL STUDY - R. HARISH; POORANA PRIYA .P (International Journal of Pharma and Bio Sciences, 2015)
Platelet parameters such as Mean platelet volume (MPV) and Platelet distribution width (PDW) are indicators of platelet activation. In cases with Rheumatoid arthritis inflammatory markers such as C-reactive protein and Erythrocyte sedimentation Rate are affected .Studies have pointed out the occurrence of changes in platelet counts in acute stages of Rheumatoid arthritis, the cause being platelets response to inflammation. Very few studies have demonstrated the relation between platelet indices and inflammatory markers. Hence we aimed to study the relation between platelet indices and acute phase reactant Erythrocyte Sedimentation Rate (ESR) .We studied a total of 100 symptomatic active cases of Rheumatoid arthritis who satisfied the diagnostic criteria. In such patients, platelet counts and indices were correlated with ESR and CRP values. In our study analysis we found an increase in platelet counts, higher values of PDW and MPV. There is statistically significant correlation between Platelet counts , Platelet distribution width and ESR.